Maximum Standardized Uptake Value of Pelvic Lymph Nodes in [18F]-Fluorodeoxyglucose Positron Emission Tomography Is a Prognostic Factor for Para-Aortic Lymph Node Recurrence in Pelvic Node–Positive Cervical Cancer Treated With Definitive Chemoradiotherapy. Issue 7 (1st September 2016) - Kim, Dong Hyun; Kim, Won Taek; Bae, Jin Suk; Ki, Yong Kan; Park, Dahl; Suh, Dong Soo; Kim, Ki Hyung; Lee, Joo Hye; Lee, Ja Young; Jeon, Ho Sang; Nam, Ji Ho
Abstract : Objectives: This study aimed to identify prognostic factors for para-aortic lymph node (PALN) recurrence and their effect on survival outcomes in patients with pelvic node–positive squamous cell carcinoma (SCC) of the cervix treated with definitive concurrent chemoradiotherapy (CCRT). Materials and Methods: Of the 116 patients with biopsy-proven SCC of the uterine cervix who underwent primary CCRT from 2007 to 2012, 48 patients with pelvic LN metastasis detected by [ 18 F]-fluorodeoxyglucose positron emission tomography (FDG PET) were retrospectively analyzed. Patients with evidence of para-aortic lymphadenopathy were excluded. The whole pelvis was the standard irradiation field for all patients. The associations of age, stage, serum SCC antigen (SCC-Ag) level, maximum standardized uptake value (SUVmax), hemoglobin level, overall treatment time, adjuvant chemotherapy, and pelvic LN status with PALN recurrence and survival outcomes were evaluated. Results: At a median follow-up of 34.0 months (range, 8–73 months), 10 (20.8%) patients had developed PALN recurrences. The relationship between pelvic LN FDG uptake and PALN recurrence was evaluated by the cutoff value (SUVmax = 3.85) determined by receiver operating characteristic curve analysis. The independent risk factors for PALN recurrence were FDG-avid pelvic LN (SUVPLN ) greater than 3.85 (hazard ratio, 13.12; P = 0.025) and posttreatment SCC-Ag level greater than 2.0 (ng/mL) (hazard ratio, 20.69; P = 0.019). Patients with an SUVPLN greater than 3.85 were found to have significantly worse 5-year distant metastasis-free (51.0% vs 79.0%, P = 0.016) and progression-free survival (38.7% vs 67.3%, P = 0.011) than those with an SUVPLN less than or equal to 3.85. Conclusions: SUVPLN is a statistically significant prognostic factor of PALN recurrence and survival after definitive CCRT for pelvic node–positive SCC of the uterine cervix.